SEMANTIC MAPPING STRATEGY ON STUDENTS’ VOCABULARY LEARNING RESULT - Reza NA; Azizah NA (Lingua, 2019)
This research entitled “The Effect of Semantic Mapping Strategy on Students’ Vocabulary Learning Resultat the Grade Ten of SMK Pusaka 1 in Academic Year of 2017/2018” principally aims to investigate whether or not Semantic Mapping Strategy significantly affects on Students’ Vocabulary Learning Result. The research samples were taken using cluster random sampling, with the total number of samples being 72 students. The location of this research was SMKPusaka 1 Jakarta. The research methodology adopted was true experimental method, with the research design being randomized post-test only control group design. To collect the data, the students were given objective test, numbering 30 items. The research data were analyzed descriptively and inferentially. The findings indicated that there was significant difference of post-test score between the students who received Semantic Mapping Strategy and students who did not receive Semantic Mapping Strategy. It can be seen from the data analysis using ANOVA that showed Fobserved (7.801) is higher than the critical value of Ftable (at the significant level of 0.05 and df = 1/70), namely 3.96. It means that Semantic Mapping Strategy has significant effect on Students’ Vocabulary Learning Result.